Kyrgyz Republic Judicial System Diagnostic : Measuring Progress and Identifying Needs - World Bank (World Bank, 2012)
The Joint Country Support Strategy for the Kyrgyz Republic (2007-2010) (JCSS), extended in 2008 to cover the period 2009-2011, identified the weak and inefficient Kyrgyz legal and judicial system as contributing to a poor business environment and weak governance. As a result, JCSS partners identified 'comprehensive judicial reform' as a program focus and a goal of the JCSS which was enlarged to include independence for the judicial budget. As part of the JCSS, the World Bank program included the preparation of a 'judicial reform study'. In order to implement this program, the World Bank and the Swiss Agency for Development and Cooperation (SDC) agreed to fund this judicial system diagnostic conducted by a World Bank diagnostic team complemented by international experts in specific sectors. The diagnostic's objective is to provide an analysis of the institutional and operational issues and obstacles that constrain the functioning of Kyrgyzstan's legal and judicial system. The diagnostic provides recommendations for overcoming key constraints both at the policy and the implementation levels.